ответ: 0 = 0
Объяснение: преобразуем последний член выражения
= ((- 1 - сtg 3π/4 · ctg2α) / (ctg3π/4- ctg2α)) ·cos4α = /cgt3π/4= -1/ =
( -(1-ctg2α) / (1+ctg2α) )· cos4α = / ctg2α = cos2α/sin2α / =(- (sin2α-cos2α) / (sin2α + c0s2α) ) · (cos²2α - sin²2α) = - (cos2α - sin2α)² = -(1-2·sin2α·cos2α) =
sin4α -1
После подстановки в исходное тождество, получим: 1-sin4+sin4α-1 =0 ч. т. д.
Тождество доказано
ответ: 0 = 0
Объяснение: преобразуем последний член выражения
= ((- 1 - сtg 3π/4 · ctg2α) / (ctg3π/4- ctg2α)) ·cos4α = /cgt3π/4= -1/ =
( -(1-ctg2α) / (1+ctg2α) )· cos4α = / ctg2α = cos2α/sin2α / =(- (sin2α-cos2α) / (sin2α + c0s2α) ) · (cos²2α - sin²2α) = - (cos2α - sin2α)² = -(1-2·sin2α·cos2α) =
sin4α -1
После подстановки в исходное тождество, получим: 1-sin4+sin4α-1 =0 ч. т. д.
Тождество доказано